2020
DOI: 10.1016/j.heliyon.2020.e03616
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of urban malaria cases due to Plasmodium falciparum and Plasmodium vivax: the case of Batu town, Oromia, Ethiopia

Abstract: Malaria is a major health problem in the world particularly in sub-Saharan Africa where 90% of malaria deaths occur. Likewise malaria is one of the leading causes of morbidity and mortality in Ethiopia. It has been reported that about 75% of the country is malarious where 60% of its population is at risk of this infection. Like many African countries, Ethiopian urban settings are characterized by poor housing, lack of sanitation and drainage of surface water which provide conducive environment for the breeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 10 publications
12
16
1
Order By: Relevance
“…Individuals in the age group of 15 and above were also more signi cantly affected. This was in line with other local studies [23,31]. Inconsistent result was observed in southern Ethiopia [24] arguing that malaria cases cluster among the under-5.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Individuals in the age group of 15 and above were also more signi cantly affected. This was in line with other local studies [23,31]. Inconsistent result was observed in southern Ethiopia [24] arguing that malaria cases cluster among the under-5.…”
Section: Discussionsupporting
confidence: 92%
“…Over the eight years period, overall, there was malaria positivity rate of 11.79%, data from the HCs. This positivity rate was comparable with certain studies done in Ethiopia including from Batu town (12.43%) [23], Arsi Negelle (11.40%) [24] and Halaba special district (9.47%) [25]. In contrast, higher overall malaria positivity rates were reported from related studies conducted in south-central Ethiopia [26], southern Ethiopia [27] and abroad in Dakar, Senegal [28] with 33.83%, 21.79% and 19.68% respectively.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, this proportion varies from place to place and season to season [7]. For example, recent studies have showed that there is a trend of shift of dominance from P. falciparum to P. vivax [9][10][11]. Since 2004, arthemisinin-lumefantrine (AL) (Coartem®) and chloroquine (CQ) are used as rst line drugs for the treatment of P. falciparum and P. vivax, respectively, in the country [7].…”
Section: Introductionmentioning
confidence: 99%